Breech deliveries in Tygerberg Academic Hospital : maternal and neonatal outcomes of vaginal and abdominal deliveries - a case-controlled study - Lindeque, L. X. (Stellenbosch : Stellenbosch University, 2011)
Thesis (MMed)--Stellenbosch University, 2011.